2000
DOI: 10.1074/jbc.275.16.11964
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structure and Characterization of Halide-binding Sites of Human Myeloperoxidase at 1.8 Å Resolution

Abstract: The x-ray crystal structure of human myeloperoxidase has been extended to 1.8 Å resolution, using x-ray data recorded at ؊180°C (r ‫؍‬ 0.197, free r ‫؍‬ 0.239). Results confirm that the heme is covalently attached to the protein via two ester linkages between the carboxyl groups of Glu 242 and Asp 94 and modified methyl groups on pyrrole rings A and C of the heme as well as a sulfonium ion linkage between the sulfur atom of Met 243 and the ␤-carbon of the vinyl group on pyrrole ring A. In the native enzyme a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
371
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(388 citation statements)
references
References 40 publications
11
371
1
5
Order By: Relevance
“…On the one hand, Lambeth's group (12) has shown that prokaryotes expressing the human Duox1 peroxidase-like region catalyzed the cross-linking of free tyrosine ethyl ester, although sequence alignment revealed that the crucial residues for catalytic activity in animal heme peroxidase, such as the distal and proximal histidines (27), are not conserved in human Duox1/2 proteins (12). However, no data have to date been reported about the activity of the homologous part of Duox2.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Lambeth's group (12) has shown that prokaryotes expressing the human Duox1 peroxidase-like region catalyzed the cross-linking of free tyrosine ethyl ester, although sequence alignment revealed that the crucial residues for catalytic activity in animal heme peroxidase, such as the distal and proximal histidines (27), are not conserved in human Duox1/2 proteins (12). However, no data have to date been reported about the activity of the homologous part of Duox2.…”
Section: Discussionmentioning
confidence: 99%
“…1B. This partial sequence alignment with the classical peroxidases demonstrates that both DUOX homologs lack the catalytic distal histidine residue (Ser 108 , hDUOX1; and Tyr 105 , CeDUOX1) and the aspartate residue that in MPO and LPO covalently binds to the heme co-factor through an ester linkage (Leu 107 , hDUOX1; and Ala 104 , CeDUOX1) (25,26). hDUOX1 lacks additional critical peroxidase residues: the glutamate that forms the second covalent bond to the heme (Arg 241 ) and the proximal histidine residue (Ser 331 ).…”
Section: Design and Expression Of Soluble Duox1mentioning
confidence: 99%
“…is the reference enzyme for the mammalian peroxidases because its crystal structure has been determined (1,22). No other mammalian peroxidase structure is available.…”
Section: Structure Superposition and Choice Of Mutations-mpomentioning
confidence: 99%
“…Mammalian peroxidases share a unique feature, the formation of two or three covalent bonds to their prosthetic heme 1 group, not found in the peroxidases of other organisms. The two common bonds in all mammalian peroxidases are ester links between a conserved glutamate and aspartate and the heme 1-methyl and 5-methyl substituents, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation